The value of analysts' recommendations in the thai stock market - Ravi Lonkani (2018)
Analysts' recommendations are especially important as they provide useful and straightforward information to investors. Using I/B/E/S data of analysts' recommendations from 1993 to 2002, we find analysts' recommendations convey similar informative 'value' to the Thai market. Our results on a calendar-time approach indicate that a momentum trading strategy is appropriate for the 'strong buy' recommendations. Our research highlights the existence of 'insider' aspects associated with the recommendations. © EuroJournals Publishing, Inc. 2010.